Tasawuf falsafi sebagai Jalan transformasi spiritual: Studi atas penerapan nilainya pada kehidupan sehari-hari - Santi, Susmita Yuliana (Maliki Interdisciplinary Journal, 2025)
Philosophical Sufism (Tasawuf Falsafi) is a branch of Sufism that combines mystical and rational approaches to understanding God and achieving inner purification through profound philosophical insight. This article aims to examine the application of the values of philosophical Sufism as a path for spiritual transformation in daily life. The method employed is a literature review, analyzing various classical and contemporary sources on the concepts, teachings, and figures of philosophical Sufism. The study reveals that philosophical Sufism not only emphasizes the purification of the soul and inner sanctity but also integrates a divine vision into everyday attitudes and behaviors, thereby shaping a spiritual character balanced between rational thought and spiritual sensitivity. The application of these values helps individuals face life’s dynamics with tranquility, awareness, and closeness to Allah SWT, while also contributing positively to social and moral life. This study underscores the importance of philosophical Sufism as a relevant path for spiritual transformation in the modern context